WUJUD TINDAK TUTUR PADA INTERAKSI PENJUAL DAN PEMBELI DI WARUNG MAKAN - Anak Agung ayu Dian Andriyani; I Dewa Ayu Devi Maharani Santika (KULTURISTIK: Jurnal Bahasa dan Budaya, 2022)
This qualitative research uses the interaction of sellers and buyers in food stalls. It aims to describe the components of speech acts and the meaning contained in the interactions. The data collected by using observation method with some techniques: recording, listening, taking notes, and interviewing the traders in food stalls. The primary data source is dialogues between sellers and buyers in ten favorite food stalls in Denpasar city and Badung district with very high buyer intensity both in the morning and in the afternoon. The analytical method used is pragmatic equivalent. The technique of presenting the results of the analysis uses ordinary words informally. The results show that the interaction between the seller and the buyer implements locutionary, illocutionary, and perlocutionary acts adjusted to the context of the situation that follows each dialogue. In addition, the meaning in the speech of the seller to the buyer are the meaning of asking, confirming, telling, and offering. These explain that although speech acts in food stalls tend to use short sentences, using too many pleasantries and the level of service provided is very limited, the interaction can run well. To avoid failure in communicating, the speech participants must have similar background knowledge.